Genetic knockdown of brain-derived neurotrophic factor in the nervous system attenuates angiotensin II-induced hypertension in mice. (March 2019) - Zhang, Zhongming; Zhang, Yijing; Wang, Yan; Ding, Shengchen; Wang, Chenhui; Gao, Li; Johnson, Alan; Xue, Baojian
Introduction: Brain-derived neurotropic factor (BDNF) is expressed throughout the central nervous system and peripheral organs involved in the regulation of blood pressure, but the systemic effects of BDNF in the control of blood pressure are not well elucidated. Materials and methods: We utilized loxP flanked BDNF male mice to cross with nestin-Cre female mice to generate nerve system BDNF knockdown mice, nestin-BDNF (+/–), or injected Cre adenovirus into the subfornical organ to create subfornical organ BDNF knockdown mice. Histochemistry was used to verify injection location. Radiotelemetry was employed to determine baseline blood pressure and pressor response to angiotensin II (1000 ng/kg/min). Real-time polymerase chain reaction was used to measure the expression of renin–angiotensin system components in the laminal terminalis and peripheral organs. Results: Nestin-BDNF (+/–) mice had lower renin–angiotensin system expression in the laminal terminalis and peripheral organs including the gonadal fat pad, and a lower basal blood pressure. They exhibited an attenuated hypertensive response and a weak or similar modification of renin–angiotensin system component expression to angiotensin II infusion. Subfornical organ BDNF knockdown was sufficient for the attenuation of angiotensin II-induced hypertension. Conclusion: Central BDNF, especially subfornical organ BDNF is involved in the maintenance of basal blood pressure and in augmentation of hypertensive response to angiotensin II through systemic regulation of the expression of renin–angiotensin system molecules.